2014
DOI: 10.3389/fpls.2014.00713
|View full text |Cite
|
Sign up to set email alerts
|

Biological mode of action of a nitrophenolates-based biostimulant: case study

Abstract: The challenges facing modern plant production involve (i) responding to the demand for food and resources of plant origin from the world's rapidly growing population, (ii) coping with the negative impact of stressful conditions mainly due to anthropopressure, and (iii) meeting consumers' new requirements and preferences for food that is high in nutritive value, natural, and free from harmful chemical additives. Despite employing the most modern plant cultivation technologies and the progress that has been made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 27 publications
(62 reference statements)
7
51
1
1
Order By: Relevance
“…Conifer needle extract (Ausma) did not influence plant growth; it even reduced the number of rhizomes of the strawberry cultivar 'Zefyr' but increased the leaf growth and the number of rhizomes of the cultivar 'Kokinskaya Pozdnaya' (Laugale et al 2006). The effect of nitrophenols (Atonic, Asahi SL) on the quality and chemical composition was ambiguous and differed depending on the tested parameter and the plant cultivar in cucumber (Przybysz et al 2014) and eggplant fruit (Majkowska-Gadomska & Wierzbicka 2013). Ascophyllumnodosum extract (Goëmar BM 86) caused an increase in fruit weight in three out of five tested raspberry cultivars, and its effect on dry matter, extract content, simple sugar content, organic acid and anthocyanins was insignificant and depended largely on growing season and cultivar (Krok & Wieniarska 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Conifer needle extract (Ausma) did not influence plant growth; it even reduced the number of rhizomes of the strawberry cultivar 'Zefyr' but increased the leaf growth and the number of rhizomes of the cultivar 'Kokinskaya Pozdnaya' (Laugale et al 2006). The effect of nitrophenols (Atonic, Asahi SL) on the quality and chemical composition was ambiguous and differed depending on the tested parameter and the plant cultivar in cucumber (Przybysz et al 2014) and eggplant fruit (Majkowska-Gadomska & Wierzbicka 2013). Ascophyllumnodosum extract (Goëmar BM 86) caused an increase in fruit weight in three out of five tested raspberry cultivars, and its effect on dry matter, extract content, simple sugar content, organic acid and anthocyanins was insignificant and depended largely on growing season and cultivar (Krok & Wieniarska 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Plant biostimulants contain substance(s) and/or micro-organisms whose function when applied to plants or the rhizosphere is to stimulate natural processes to enhance/benefit nutrient uptake, nutrient efficiency, tolerance to abiotic stress, and crop quality [13]. The use of foliar biostimulants in agriculture is relatively recent but few studies published to date have shown biostimulants to have a positive effect on yield in several crops, oilseed rape [14], cotton [15], bean [16], and carrot [17]. Using biostimulants makes it possible to reduce the amount of fertilizer thereby reducing the negative impact of the crop on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Natural bio-stimulants are preparations based on free amino acids, seaweed and fruit extract, effective microorganisms, humic substances and chitosan (Calvo et al, 2014;Kocira et al, 2015a;Kocira et al, 2015b). Synthetic plant stimulants include growth regulators, preparations containing phenolic compounds, inorganic salts, essential elements, and other substances (Przybysz et al, 2014;Kocira et al, 2015c;Kocira et al, 2015d).…”
Section: Introductionmentioning
confidence: 99%